Bioengineering an Osteoinductive Treatment for Bone Healing Disorders: A Small Animal Case Series - Marshall, William G.; Gonzalez-Garcia, Cristina; Trujillo, Sara; Alba-Perez, Andres; Childs, Peter; Shields, David W.; Tomlinson, Andrew; Pettitt, Rob; Filliquist, Barbro; Chou, Po-Yen; Dalby, Matthew J.; Corr, Sandra A.; Salmeron-Sanchez, Manuel (VCOT Open, 2023)
The aim of this article was to study clinical and radiographic outcomes following treatment of bone healing disorders with a novel osteoinductive system that utilizes poly (ethyl acrylate), fibronectin and an ultra-low concentration of recombinant human bone morphogenetic protein-2. A case series of nine dogs and two cats were treated, and clinical records and radiographs were reviewed. Radiographs were scored by two blinded observers using the modified Radiographic Union Score for Tibial Fractures. Long-term follow-up was obtained using the Canine Orthopaedic Index and Feline Musculoskeletal Pain Index. Follow-up data were available for 11 treatments (10 cases). Complications: three minor, three major, one catastrophic (non-union requiring amputation). Lameness median 320 (range: 42–1,082) days postoperatively: ‘sound’ (three cases), ‘subtle’ (two), ‘mild’ (three), ‘moderate’ (one), and ‘non-weightbearing’ (one). The attending clinician judged 9 of 11 treatments achieved radiographic union; modified Radiographic Union Score for Tibial Fractures observers 1 and 2 agreed with the clinician in 8/9 and 5/9 treatments respectively. Long-term Canine Orthopaedic Index scores for five dogs median 650 (range: 544–1,724) days postoperatively: 15/64 (median) for four dogs with acceptable outcomes, 30/64 in one dog with a poor outcome. Feline Musculoskeletal Pain Index scores for two cats 433 and 751 days postoperatively: 48/60 and 60/60. Eight of 10 cases were sound or showed subtle or mild lameness in the short- or long-term, and radiographic union occurred in the majority of treatments.
Keywords: bioengineering; bone morphogenetic protein; cats; dogs; fracture healing